Tracing the dual-circulation value chain: Measurement on the embedding characteristics and evidence from China - Yi Ren; Jinniu Zhang; Yuan Tian (Journal of Urban Management)
The rational allocation of value chain space can effectively promote regional development. In China, various regions have optimized their National Value Chain (NVC) by participating in the Global Value Chain (GVC), forming a structure of Dual-Circulation Value Chain (DCVC) dominated by NVC. This study aims to integrate multiple analytical models to construct an analytical method for studying the DCVC, thereby addressing the existing gaps in the literature in this field. When considering each province in China as the research subject, the following conclusions can be drawn: ①Point analysis results indicate that provinces such as Beijing and Jiangsu excel in connecting domestic and international markets, while resource-rich regions like Tibet and Xinjiang exhibit lower coupling between the NVC and the GVC. Coastal cities such as Shanghai and Guangdong are primarily situated in the mid-to-downstream segments, closely linked to the GVC; in contrast, resource-rich areas like Xinjiang and Shanxi predominantly occupy upstream positions. The effects of value creation and value transfer contribute to the relatively low value rate of return in provinces such as Beijing and Jiangsu. ②Area analysis further reveals that the coupling degree of the dual circulation value chain presents an east-to-west gradient, with domestic circulation as the dominant component, gradually forming a structure centered on the domestic cycle. The division of labour in the value chain is linear: inland areas focus on upstream resource production, central regions emphasize primary processing, and coastal areas are concentrated in downstream manufacturing and trade. Overall, the value chain return decreases from west to east, indicating that despite higher production levels in coastal regions, actual profits remain relatively low.